2020
DOI: 10.1186/s12875-020-01253-3
|View full text |Cite
|
Sign up to set email alerts
|

Episodes of care in a primary care walk-in clinic at a refugee camp in Germany – a retrospective data analysis

Abstract: Background From 2015 to 2016 Germany faced an influx of 1.16 million asylum seekers. In the state of Hamburg Primary Care walk-in clinics (PCWC) were commissioned at refugee camps because the high number of residents (57,000 individuals) could not be provided with access to regular healthcare services. Our study aims were (1) to describe the utilization of a PCWC by camp residents, (2) to compare episodes of continuous care with shorter care episodes and (3) to analyse which diagnoses predict episodes of conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…It can be assumed that the refugees have only slowly integrated into the general practices. 22 Therefore, the patient types ‘patients with migration background and culturally different disease concepts’ and ‘patients with migration background and communication problems’ could be nowadays found more frequently in general practices. It could also affect other patient types like ‘patients with psychiatric problems’, which are frequently found in the refugee population.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that the refugees have only slowly integrated into the general practices. 22 Therefore, the patient types ‘patients with migration background and culturally different disease concepts’ and ‘patients with migration background and communication problems’ could be nowadays found more frequently in general practices. It could also affect other patient types like ‘patients with psychiatric problems’, which are frequently found in the refugee population.…”
Section: Discussionmentioning
confidence: 99%
“…4 10 17-26 Nineteen studies assessed the impact of EHRs on health outcomes in populations after arriving in an asylum country. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Quality assessment of included studies According to the critical appraisal tools described in the methods section, 20 articles were of medium-high quality, nine were of medium quality and three were low-quality. The qualitative studies demonstrated acceptable methodological quality but did not report on the influence of the researcher.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Nineteen studies assessed the impact of EHRs on chronic disease health outcomes for asylum seekers. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The uses of EHRs in these studies ranged from screening measures to characterising the chronic diseases in a population to improving guidelines and reducing the health disparities in asylum populations compared with the general population. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Several studies commented on the utility of EHRs as screening tools for asylum populations.…”
Section: Impact In Asylum Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…High prevalence rates of scabies infestation 3 , reports of outbreaks of measles 4 , 5 and varicella 6 – 8 and protozoa infections 9 have been described in this population. Acute respiratory infections are among the most common reasons for seeking primary medical care among refugees, migrants, and nonmigrants in Germany 10 .…”
Section: Introductionmentioning
confidence: 99%